PERANCANGAN DESAIN KARAKTER UNTUK ANIMASI " KARTA THE LEGEND OF CIKONDANG VILLAGE " SEBAGAI UPAYA MENCIPTAKAN MEDIA VISUAL PENGETAHUAN REMAJA 12-21 TAHUN AKAN KEBUDAYAAN KAMPUNG ADAT CIKONDANG - Ananda, Ahmad Rafi Hanif; Mario, Mario; Sumarlin, Rully (eProceedings of Art & Design, 2025)
Abstract : For teenagers, tourist attractions become things that are quickly loved, apart from just following the existing trends, teenagers will also be interested in a tourist spot that is able to provide its attractiveness. To introduce a tourist spot, of course a promotional media is needed, the problem faced by cultural-themed tourist attractions usually lies in the mindset of teenagers who think cultural tourism is boring, for that a knowledge media is needed that serves to provide knowledge as well as to promote cultural tourism, such as to introduce the Cikondang Traditional Village Cultural Heritage to teenagers. This research is a qualitative descriptive research. The data used is primary data obtained from direct interviews with teenagers and sources from Cikondang Traditional Village, as well as several experts in the field of culture. Data collection techniques using interviews, observation, and documentation techniques. Data analysis techniques in this study are data reduction, data presentation, data analysis and conclusion drawing. This research aims to find out how ways and efforts to provide knowledge, as well as promote to teenagers so that they can recognize what Cikondang Traditional Village is, what culture is there and the impact they get when they know and learn all about Cikondang Traditional Village. Keywords: teenagers, Culture, Cikondang Traditional Village